STUDI BICULTURAL ETNIS JAWA, TIONGHOA, DAN BATAK PADA PT KARYA TEKHNIK UTAMA DI KOTA BATAM - TENGKU FENNY RIFALNY ALJUFRY; SHOHILUL ABIDIN (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Cultural background can affect how people communicate with the others, this alsohappens in organizational context. Cultural diversity that exists in an organization affects theway of organization members communication. This also happened at PT. Karya TekhnikUtama which has employess from various cultural backgrounds such as Javanese, Chinese,and Bataknese. The success of an organization is inseparable from the process ofcommunication between individuals who come from different cultural backgrounds in thecontext of their work. This research emphasizes the study of Javanese, Chinese, andBataknese ethnic biculturalism at PT. Karya Tekhnik Utama in Batam City.This research uses a qualitative ethnographic approach. Data collection in this studywas conducted by interview and observation methods. The results showed that both Javanese,Chinese, and Bataknese when in the context of the work environment tended to try to adjustthe norms in the organization such as adapting to the work environment and tended to useways that were acceptable to the environment in resolving conflicts and expressing opinions